Analysis of the Mouse Transcriptome for Genes Involved in the Function of the Nervous System - Gustincich, Stefano; Batalov, Serge; Beisel, Kirk W.; Bono, Hidemasa; Carninci, Piero; Fletcher, Colin F.; Grimmond, Sean; Hirokawa, Nobutaka; Jarvis, Erich D.; Jegla, Tim; Kawasawa, Yuka; LeMieux, Julianna; et al. (Genome Research, 2003)
We analyzed the mouse Representative Transcript and Protein Set for molecules involved in brain function.We found full-length cDNAs of many known brain genes and discovered new members of known brain gene families, including Family 3 G-protein coupled receptors, voltage-gated channels, and connexins.We also identified previously unknown candidates for secreted neuroactive molecules.The existence of a large number of unique brain ESTs suggests an additional molecular complexity that remains to be explored.A list of genes containing CAG stretches in the coding region represents a first step in the potential identification of candidates for hereditary neurological disorders.
10.1101/gr.1135303